1998
DOI: 10.1006/viro.1998.9055
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of Human Sera with Human Herpesvirus-8-Infected BCBL-1 Cells and Identification of HHV-8-Specific Proteins and Glycoproteins and the Encoding cDNAs

Abstract: The reactivates of human sera with uninduced and phorbol ester (TPA)-induced human herpesvirus-8 (HHV-8)-infected BCBL-1 cells were examined by immunofluorescence assay (IFA) and by radioimmunoprecipitation reactions (RIP). The seroprevalence of HHV-8 infections is low in the United States general population and only low levels of HHV-8 antibodies were detected in the seropositive sera. In contrast, high levels of antibodies against HHV-8 lytic and latent antigens were detected by IFA in the sera from HIV+ Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
0
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 27 publications
3
51
0
2
Order By: Relevance
“…Previous studies have shown that the detection of HHV-8 antibodies for lytic proteins was generally more sensitive than the detection of HHV-8 DNA in peripheral blood mononuclear cells for the assessment of HHV-8 infections in HIVinfected patients with KS (13,33). By contrast, some authors (15,28) have found HHV-8 DNA by PCR in bone marrow stromal cells obtained from patients with multiple myeloma in whom HHV-8-specific antibodies had not been detected.…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 98%
“…Previous studies have shown that the detection of HHV-8 antibodies for lytic proteins was generally more sensitive than the detection of HHV-8 DNA in peripheral blood mononuclear cells for the assessment of HHV-8 infections in HIVinfected patients with KS (13,33). By contrast, some authors (15,28) have found HHV-8 DNA by PCR in bone marrow stromal cells obtained from patients with multiple myeloma in whom HHV-8-specific antibodies had not been detected.…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 98%
“…More recently, using uninduced and TPA-induced BCBL-1 cells 35 , IFA antibody titers to HHV-8 were found to be much higher in HIVinfected Los Angeles patients with KS than in those HIV-infected without KS; furthermore, antibody positivity rate was 8% in healthy individuals, 56% in HIV-positive homosexual men, and 12% in age-matched HIV-negative controls 36 .…”
Section: Epidemiology Of Hhv-8 Infection -Serological Datamentioning
confidence: 98%
“…Sera of patients with KS contain high titers of antibodies to both latent and lytic cycle viral products (1,8,9,15,17,22,27,35). Although the majority of tumor cells are latently infected, some spindle cells and monocytic cells in the KS lesions express lytic cycle products, including chemokines and proinflammatory cytokines encoded by KSHV (4,24,25,36,37,41).…”
mentioning
confidence: 99%